Crop management to enhance plant resilience to abiotic stress using nanotechnology: towards more efficient and sustainable agriculture - Al-Dossary, Othman; Alnaddaf, Lina M.; Al-Khayri, Jameel M. (Frontiers in Plant Science, 2025)
Nanotechnology has become a transformative tool in modern agriculture, playing a pivotal role in enhancing crop resilience to abiotic stresses, including drought, salinity, and extreme temperatures. As global population growth and environmental challenges place increasing pressure on agricultural systems, nanotechnology plays a crucial role in enhancing crop yields and ensuring long-term sustainability. Nanotechnology, through advanced applications, optimizes nutrient delivery, strengthens plant defense mechanisms, and enables precise monitoring of environmental conditions. These innovations enhance soil quality, regulate physiological responses in plants, and mitigate the adverse effects of environmental stressors, thereby promoting sustainable farming practices and improving food production efficiency. Nanoparticles (NPs), synthesized through green methods using plant or microbial extracts, have shown promise in enhancing stress tolerance by facilitating uptake, translocation, and intracellular movement within plants. Major factors influencing NPs efficacy include size, concentration, composition, and duration of exposure. Biosensors and nanobiosensors provide prognostic tools for real-time detection and management of plant stress. Despite their potential benefits, the use of nanotechnology in agriculture raises concerns regarding environmental and health impacts. The accumulation of NPs in soil and aquatic ecosystems may affect microbial diversity, disrupt soil enzymatic activity, and alter plant–microbe interactions, posing risks to non-target organisms and overall ecosystem health. Moreover, variability in plant responses to NPs complicates the development of standardized application protocols. Therefore, its successful adoption relies on sustained interdisciplinary research, ethical oversight, and the development of sound policy frameworks. This integrated approach is crucial for developing resilient, efficient, and sustainable agricultural systems that can meet future challenges.